2014
DOI: 10.1002/mrm.25218
|View full text |Cite
|
Sign up to set email alerts
|

Rapid-Steady-State-T1signal modeling during contrast agent extravasation: Toward tumor blood volume quantification without requiring the arterial input function

Abstract: Straightforward tumor BVf quantification without AIF determination is demonstrated in presence of CA leakage. The method will facilitate angiogenesis assessment in longitudinal neuro-oncologic studies in particular when monitoring the response to antiangiogenic therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…[21] In another respect, the whole blood accounts for 8% of the body weight. It was reported that blood volume fraction (BVf) in tumor is 3.4 AE 0.5%.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…[21] In another respect, the whole blood accounts for 8% of the body weight. It was reported that blood volume fraction (BVf) in tumor is 3.4 AE 0.5%.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…1(d)]. Consequently, its BVf needs to be calculated using kinetic modeling 16 and results in a BVf of 0.4-0.11 in the tumor rim [ Fig. 1(e)].…”
Section: A Patientsmentioning
confidence: 99%
“…1(a) in Ref. 16] resulting from the short TI and TR, water exchange has less impact on BVf quantification than conventional dynamic or steady state techniques. 32 BVf overestimation can be kept within 10% by adjusting the injected CA dose in such a way that the CA concentration in blood reaches the required threshold without being unnecessarily high.…”
Section: B Water Exchangementioning
confidence: 99%
See 2 more Smart Citations